2017
DOI: 10.1101/181743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Rho-GTPase based model explains spontaneous collective migration of neural crest cell clusters

Abstract: We propose a model to explain the spontaneous collective migration of neural crest cells in the absence of an external gradient of chemoattractants. The model is based on the dynamical interaction between Rac1 and RhoA that is known to regulate the polarization, contact inhibition and co-attraction of neural crest cells. Coupling the reaction-diffusion equations for active and inactive Rac1 and RhoA on the cell membrane with a mechanical model for the overdamped motion of membrane vertices, we show that co-att… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 64 publications
(115 reference statements)
1
13
0
Order By: Relevance
“…There are many prior computational studies of individual and collective cell migration, incorporating a wide range of biophysical detail (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). For example, Zaman and colleagues minimally model individual cell migration, integrating a force-based model of an individual cell with the interactions between cellular and extracellular mechanical forces and extracellular matrix signaling (21)(22)(23).…”
Section: Prior Computational Studies Of Cell Migrationmentioning
confidence: 99%
“…There are many prior computational studies of individual and collective cell migration, incorporating a wide range of biophysical detail (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). For example, Zaman and colleagues minimally model individual cell migration, integrating a force-based model of an individual cell with the interactions between cellular and extracellular mechanical forces and extracellular matrix signaling (21)(22)(23).…”
Section: Prior Computational Studies Of Cell Migrationmentioning
confidence: 99%
“…23 More recent studies suggest that cell polarization is also crucial for successful cell invasion but it is naturally induced by CiL and CoA, which are modulated by dynamical interactions of Rac1 and RhoA. 24 Studies of chick NC cell migration reveal that the main migratory driving forces for these cells vary across different axial levels and involve chemotaxis. Simpson et al 25 investigated the main mechanisms regulating successful invasion and colonization of the gut by vagal NC cells in chick embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, net movement of the two populations results (2016) for specific reviews on the modelling of neural crest dynamics, and to Camley and Rappel (2017) for a review of collective cell migration models in general. With regard to CIL phenomena, one-to-one interactions between migrating and colliding NCs within quasi-one-dimensional geometries have been modelled in Kulawiak et al (2016) and Merchant et al (2018). The former developed a computational phase field model, explicitly accounting for cell shape and intracellular biochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with experimental observations by Scarpa et al (2013), different collision outcomes were observed (reversals, sticking and walk-past) according to the balance of different factors, such as adhesion. The model by Merchant et al (2018) also investigated the outcome of collisions along 1D lines, in a model where each cell's membrane is represented by a closed chain of elastic edges. Rac1/RhoA biochemistry was included via kinetic equations, with CIL and a NC-NC co-attraction process (mediated via the complement factor C3a and its receptor C3aR, see Carmona-Fontaine et al 2011) incorporated through their action on kinetic terms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation